The students' self perception on learning C++ programming via the cryptography project: a case study - Kamarudin, Shafinah; Punzalan, Christopher; Derahman, Mohd Noor; Mohd, Siti Munirah; Mohd Jan, Nurhidaya; Abdul Wahab, Amelia Natasya (Human Resource Management Academic Research Society, 2022)
C++ programming course is among the most common programming subjects offered in tertiary education. Students’ programming skills and other soft skills can be enhanced by adopting a project-based learning approach to the topic of Cryptography. Furthermore, students should be exposed to cryptography since security, confidentiality, and data privacy are key concerns in the communication world. Therefore, this study aims at identifying the students' self-perception of learning C++ programming through a project related to Cryptography. This project was assigned to the students who enrolled in the C++ programming course at Universiti Putra Malaysia in Semester 2, session 2020/2021. Finally, all students are capable of completing and demonstrating their projects. A survey questionnaire is delivered to indicate the students' perception of their programming skills, other soft-skill, and their knowledge of Cryptography. Since this course was conducted online, students were requested to list their challenges in completing this project. Through this approach, students positively perceive improving their programming skills and other soft skills and gaining knowledge about Cryptography. Overall, the selected theme related to the student’s major field is recommended.